SYNAPSES IN THE CENTRAL NERVOUS SYSTEM - Palay, Sanford L. (The Rockefeller University Press, 1956)
A number of different synapses have been described in the medulla, cerebellar cortex, and cerebral cortex of the rat. All of these possess the same fundamental fine structure as follows: 1. Close apposition of the limiting membranes of presynaptic and postsynaptic cells without any protoplasmic continuity across the synapse. The two apposed membranes are separated by a cleft about 200 A wide, and display localized regions of thickening and increased density. 2. The presynaptic expansion of the axon, the end-foot or bouton terminal, contains a collection of mitochondria and clusters of small vesicles about 200 to 650 A in diameter. Although the significance of these structures in the physiology of the synapse is still unknown, two suggestions are made: that the mitochondria, by means of the relation between their enzymatic activity and ion transport, participate in the electrical phenomena about the synapse; and that the small synaptic vesicles provide the morphological representation of the prejunctional, subcellular units of neurohumoral discharge at the synapse demanded by physiological evidence.